Psychological and Educational Interventions for Atopic Dermatitis in Adults: A Systematic Review and Meta-Analysis. Issue 1 (8th May 2017) - Hashimoto, Kayoko; Ogawa, Yusuke; Takeshima, Nozomi; Furukawa, Toshi A.
Abstract : Psychological and educational interventions are valuable adjuncts in the management of adult atopic dermatitis. We performed a systematic review and meta-analysis of randomised controlled trials (RCTs) of the efficacy of these interventions. Twelve articles published between 1986 and 2013 were identified through electronic searches. The methodological quality was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions, version 5.1.1 (Higgins & Green, 2015). A random-effects model was used to estimate the standardised mean difference (SMD). No significant difference was found in eczema severity determined in three RCTs (124 participants; SMD, -0.29; 95% CI [-0.64, 0.07]) and dropout rate in five RCTs (198 participants; relative risk, 0.66; 95% CI [0.20, 2.17]). Education via online video was significantly superior to handouts in ameliorating eczema severity in one RCT (80 participants). We conclude that, rather than a combination of these interventions with conventional therapy being of no value, the data did not have sufficient power to provide evidence-based conclusions.